Efficient Biosynthesis of (2 S )-Naringenin from p -Coumaric Acid in Saccharomyces cerevisiae - Gao, Song; Lyu, Yunbin; Zeng, Weizhu; Du, Guocheng; Zhou, Jingwen; Chen, Jian (Journal of agricultural and food chemistry, 2020)
(2 )-Naringenin, a (2 )-flavanone, is widely used in the food, chemical, and pharmaceutical industries because of its diverse physiological activities. The production of (2 )-naringenin in microorganisms provides an ideal source that reduces the cost of the flavonoid. To achieve efficient production of (2 )-naringenin in ( ), we constructed a biosynthetic pathway from -coumaric acid, a cost-effective and more efficient precursor. The (2 )-naringenin synthesis pathway genes were integrated into the yeast genome to obtain a (2 )-naringenin production strain. After gene dosage experiments, the genes negatively regulating the shikimate pathway and inefficient chalcone synthase activity were verified as factors limiting (2 )-naringenin biosynthesis. With fed-batch process optimization of the engineered strain, the titer of (2 )-naringenin reached 648.63 mg/L from 2.5 g/L -coumaric acid. Our results indicate that the constitutive production of (2 )-naringenin from -coumaric acid in is highly promising.